Study the Immune Response of Conjunctival Vaccinated Sheep and Goats with Locally Produced S19 Vaccine for Controlling the Brucellosis: Waffa A.A.1 and G.M. AL-Khatib2 - احمد وفاء عبدالاله (The Iraqi Journal of Veterinary Medicine, 2012)
Two flocks of sheep and goats (30 and 35 animals) were vaccinated by locally produced S19 vaccine, each animal instilled with 2 X 109 cfu in each drop conjunctively. From each flock, a group of 10 heads was used to study the immune response serologically at intervals 2, 4, 6, 8, and 19 week through blood samples using the rose bengal plate test (RBPT) and serum agglutination test (SAT) to determine Ab titres. The results of RBPT were 100% positive till 6 and 8 weeks in sheep and goats respectively, while SAT showed means of Ab titer after vaccination 100, 84, 47, 21, and 7 in sheep while in goats reached 144, 192, 100, 62, and 13. Also, the cellular immune response was evaluated by prepared Peptidoglycan Brucellin (PGB), which was injected in 10 guinea pigs through 4 concentrations 10, 100, 200, and 500 µg, 200 µg was used in brucellin test at the sixth and thirteenth week after vaccination, the antigen caused erythemia and induration in the vaccinated sheep and goats while the test give negative results in non-vaccinated animals. The study revealed that the conjunctival route is more safe, easy, and economic, and also the rapid reduce of Abs titer compared with subcutaneous route. Also, it is noticed that there were no side effects in the conjunctival route comparatively with subcutaneous route such as inflammation, abscess, and screw worm in the worm infestation in the site of injection. The study concluded the possibility of using conjunctival route in the vaccination campaign for controlling brucellosis in sheep and goats and also possibility of using one vaccine for different field animals against brucellosis.